Trial of Phenoxymethylpenicillin, Phenethicillin, and Lincomycin in Treatment of Staphylococcal Sepsis in a Casualty Department. Issue 5615 (17th August 1968) - Price, D. J. E.; O'Grady, F. W.; Shooter, R. A.; Weaver, P. C.
Abstract : A comparative trial of phenoxymethylpenicillin (penicillin V), phenethicillin (Broxil), and lincomycin (Lincocin) against superficial staphylococcal infections seen in a casualty department showed no difference in the efficacy of the three agents, though half the staphylococci isolated were resistant to penicillin. Possible reasons include the fact that antibiotic treatment may not affect superficial staphylococcal infections, or that the organisms concerned may have been weak formers of penicillinase. Half the patients treated with lincomycin complained of diarrhoea and 5% of those treated with phenethicillin suffered from nausea.